Quorum Systems towards an Asynchronous Communication in Cognitive Radio Networks - Sylwia Romaszko; Petri Mähönen (Journal of Electrical and Computer Engineering)
This paper reviews quorum systems (QS) from the perspective of cognitive radio networks. Quorum systems were originally developed for and widely used in the scope of operating systems. Recently, quorum systems have been also started to be applied to wireless communications. The objective of this paper is threefold. First, the paper provides survey and guidance on the use of quorum systems. Second, it shows that QS properties provide an interesting alternative towards an asynchronous communication in cognitive radio ad hoc networks (CRANs). Due to properties of quorum systems it is possible to establish CRANs without employing a common control channel (CCC), perfect synchronization, or central controller architecture. QS properties can be efficiently utilized to handle the rendezvous (RDV) problem in CRANs. New RDV protocols must be designed in such a way that there is a guarantee that all nodes meet periodically within reasonable periods of time. Since pseudorandom solutions do not provide this guarantee, systematic approaches are needed such as QSs. Third, we also propose a novel distributed RDV protocol, MtQS-DSrdv, which is based on mirror torus QS and difference set concepts. The proposed protocol guarantees RDVs on all available channels while CR nodes have the same channel set.